Acute stress decreases serotonin transporter mRNA in the raphe pontis but not in other raphe nuclei of the rat - Vollmayr, Barbara; Keck, S; Henn, Fritz A.; Schloss, Patrick (Neuroscience letters, 2000)
In addition to elevated corticosterone levels, stress produces structural changes and neuronal damage especially in the hippocampus. In this line it has been shown, that in rats single or repeated immobilisation markedly reduces brain-derived neurotrophic factor (BDNF) mRNA levels in the hippocampal formation. Since this neurotrophin also controls the efficacy of serotonergic neurotransmission, the aim of the current study was to investigate the effect of acute immobilization stress on the expression of serotonin transporter (SERT) mRNA in the raphe nuclei as a parameter of serotonergic innervation. We have examined the expression of SERT mRNA and of BDNF mRNA in rats upon acute immobilisation by quantitative in situ hybridisation with a 35S-labelled oligonucleotide probe. Elevated corticosterone levels in stressed animals confirmed as internal controls the effect of stress under our conditions. Acute stress led to a significant decrease of BDNF mRNA in the hippocampus and of SERT mRNA in the raphe pontis, but not in other raphe nuclei investigated. These data provide evidence for fast interactions between neurotrophins, corticosterone and serotonergic neurotransmission under stress conditions.
Gesehen am 12.11.2020